Controlling the fire — tissue‐specific mechanisms of effector regulatory T‐cell homing. Issue 4 (13th January 2015) - Chow, Zachary; Banerjee, Ashish; Hickey, Michael J
Abstract : Regulatory T cells have essential roles in regulating immune responses and limiting inappropriate inflammation. Evidence now indicates that to achieve this function, regulatory T cells must be able to migrate to the most appropriate locations within both lymphoid and non‐lymphoid organs. This function is achieved via the spatiotemporally controlled expression of adhesion molecules and chemokine receptors, varying according to the developmental stage of the regulatory T cell and the location and environment where they undergo activation. In this Review, we summarise information on the roles of adhesion molecules and chemokine receptors in mediating regulatory T‐cell migration and function throughout the body under homeostatic and inflammatory conditions. In addition, we review recent studies that have used in vivo imaging to examine the actions of regulatory T cells in vivo, in lymph nodes, in the microvasculature and in the interstitium of peripheral organs. These studies reveal that the capacity of regulatory T cells to undergo selective migration serves a critical role in their ability to suppress immune responses. As such, the cellular and molecular requirements of regulatory T‐cell migration need to be completely understood to enable the most effective use of these cells in clinical settings. Abstract : The April 2015 issue contains a Special Feature on "Chemokines in cellular positioning and human disease". Chemokines serve as critical extracellular mediators of cell migration and retention. Recent studies have highlighted the importance of how cells are positioned within peripheral and lymphoid tissues for the development of timely effector and memory responses. In addition, advances in structural determination of chemokine receptor‐ligand complexes and the identification of genetic mutations that impact cell migration have brought us closer to targeting this system for the development of new anti‐inflammatory and anti‐tumor based drugs. Immunology and Cell Biology thanks the coordinator of this Special Feature ‐ Joanna Groom ‐ for her planning and input.